Analisis Sektor Unggulan Provinsi Jawa Timur: Shift Share and Location Quotient Analysis - Dyah Puspitasari; Rian Dwi Utami (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The leading sector is an important sector for every region to know because it can be used by the Regional Government to explore regional potential. This research analyzes the leading sectors in East Java Province using the shift share and location demand analysis approaches from 2017-2021. Based on data processing that has been carried out, it is known that there are several leading sectors in East Java with advanced and rapidly growing criteria, namely the processing industry sector, water supply, waste management, waste and recycling, wholesale and retail trade; car and motorbike repairs, provision of accommodation and food and drink; information and communication. Therefore, local governments must maximize the economy with these superior sectors.